The Influence of Parenting Styles on Early Childhood in Shaping Children's Morality in the Bintaldam XIV Unit - Firman, Firman; H. M. Ghalib; Saprin (Jurnal Mercusuar, 2021)
This research discusses the Influence of Parenting Style on Early Childhood Towards the Development of Children's Character in Bintaldam XIV/Hasanuddin Makassar unit. The main problem discussed is the extent of the influence of parenting style on early childhood towards the development of children's character in Bintaldam XIV/Hasanuddin Makassar unit. This research is a quantitative study with a survey research category, using a positivistic methodological approach and a pedagogical scientific approach. The research population consisted of 63 people, with a sample of 63 personnel. The sampling technique used was saturated sampling, which means all members of the population were used as samples in the study. Data were collected using a questionnaire as a data collection instrument. Data processing and analysis techniques used descriptive and inferential statistics, with simple linear regression analysis. The results showed that parenting style in early childhood in Bintaldam XIV/Hasanuddin Makassar unit was in the conducive category with a percentage of 82% from the established criteria. The implications of this research are 1) The development of children's character should be done as early as possible when the child is still in early childhood with good parenting style because educating children at an early age has a strong influence on children; 2) The development of children's character is not only by commanding or ordering, but it should also be accompanied by good role models from parents; and 3) Parenting styles for early childhood should be carried out by combining authoritarian, democratic, and permissive parenting styles according to the child's age and condition.